Cognition and Academic Performance: Mediating Role of Personality Characteristics and Psychology Health - Shi, Yueqi; Qu, Shaowei (Frontiers in Psychology, 2021)
This study uses personality and psychology health characteristics of high school students as intermediary variables to study how cognitive ability affects academic performance, and analyzes memory, information processing, presentation, logical reasoning, and thinking transformation ability in high school students. The participants were 572 high school students from Beijing, China. They completed a survey that included questions on cognitive ability, personality characteristics, and psychology health. This study uses structural equation modeling for mediation analysis, the results of the study showed that memory, information processing, presentation, logical reasoning, and thinking conversion ability can all positively predict academic performance. However, after considering the mediating role of personality characteristics and psychology health, the direct effect of cognitive ability on academic performance is no longer found to be significant, personality characteristics and psychology health play a complete mediating role between cognitive ability and academic performance.